Bellingcat funded by US and UK intelligence contractors that aided extremists in Syria - Klarenberg, Kit (The Grayzone, 2021)
Bellingcat is funded by scandal-ridden US and UK intelligence contractors that supported violent jihadists in Syria, while reaping profits.